Sequential 2.5 mg letrozole/FSH therapy is more effective for promoting pregnancy in infertile women with PCOS: a pragmatic randomized controlled trial - Chen, Li-Juan; Liu, Yi; Zhang, Ling; Li, Jing-Yi; Xiong, Wen-Qian; Li, Tao; Ding, Hui; Li, Bing-Jie (Frontiers in Endocrinology, 2024)
In infertile women with polycystic ovary syndrome (PCOS), is the sequential use of letrozole 2.5 mg/follicle stimulating hormone(FSH) more effective than letrozole 5 mg/FSH in stimulating ovulation and promoting pregnancy?Research design and methods:The study was designed as a prospective, single-centre, randomised, controlled pragmatic clinical trial. 220 infertile women between the ages of 20 and 40, who matched the Rotterdam criteria for PCOS and had no other identified reasons for infertility were enrolled from April 2023 to July 2023.The participants were randomly assigned to two groups in a 1:1 ratio. One group received 2.5 mg of letrozole on cycle days 3-7 with a sequential injection of 75 IU FSH on cycle days 8-10 (n = 110), while the other group received 5 mg of letrozole on cycle days 3-7 with a sequential injection of 75 IU FSH on cycle days 8-10 (n = 110). The duration of FSH treatment varied depending on the follicular development stage. Each participant underwent one to three treatment cycles until achieving pregnancy.The primary outcome was the cumulative pregnancy rate of all the participants. Secondary outcomes included characteristics and clinical pregnancy rates of all the intervention cycles.Results:For all 220 participants, the sequential letrozole 2.5 mg/FSH treatment group had a significantly higher cumulative pregnancy rate compared to the letrozole 5 mg/FSH treatment group (72.7% versus 59.1%, RR (95%CI) = 1.23 (1.02, 1.49), P-value = 0.033). For all 468 intervention cycles, letrozole 2.5 mg/FSH group had a significantly higher clinical pregnancy rate than the letrozole 5 mg/FSH group (36.2% versus 26.3%, P-value = 0.021), no statistically significant differences were observed in ovulation rates or adverse effects.The data indicate that the sequential letrozole 2.5mg/FSH protocol may be more effective than the sequential letrozole 5mg/FSH protocol for promoting pregnancy in infertile women with PCOS. This is a provisional file, not the final typeset article Clinical trial registration: www.chictr.org.cn, identifier ChiCTR2300069638.